Czech Republic : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Following a severe and protracted recession, a modest economic recovery has taken hold in the Czech Republic. Economic growth turned modestly positive after the first quarter of 1999, headed by a rebound in household consumption and a recovery of demand in European Union (EU) trading partners. However, investment remained weak owing to banking and corporate sector restructuring. Executive Directors agreed that macroeconomic policies needed to strike a balance between sustaining the pace of recovery and making progress toward achieving medium-term policy objectives.